Pengaruh Servant Leadership dan Budaya Organisasi Terhadap Kinerja Tenaga Kesehatan Rumah Sakit Umum Daerah Ciawi Kabupaten Bogor - Romadhonal Qodarul Akbar; Adriza; Widya Nengsih (MES Management Journal, 2025)
Improving the performance of health workers is a key focus in hospital management, especially amidst increasing demands for public health services. Ciawi Regional Public Hospital (RSUD) in Bogor Regency, as a referral health facility, faces challenges in maintaining service quality while dealing with limited human resources and high workloads. The phenomenon of heavy workloads and the need for servant leadership and a supportive organizational culture underlies the importance of this study. This research aims to analyze the influence of Servant Leadership and Organizational Culture on the Performance of Health Workers at Ciawi RSUD. The study uses a quantitative method with data collected through literature review and questionnaires distributed to respondents. The population in this study consists of 441 nurses at RSUD Ciawi, with a sample size of 110 nurses selected using proportional random sampling. Data were analyzed using simple and multiple linear regression, correlation analysis, and coefficient of determination. The results show that Servant Leadership has a moderate relationship with health worker performance, with a correlation coefficient (R) of 0.587 and a determination coefficient (R²) of 0.345, indicating that 34.5% of performance is influenced by Servant Leadership. Meanwhile, Organizational Culture shows a strong relationship with performance, with R = 0.744 and R² = 0.553, meaning 55.3% of performance is influenced by Organizational Culture. Simultaneously, Servant Leadership and Organizational Culture significantly affect health worker performance with a correlation coefficient (R) of 0.782 and R² = 0.611, indicating that 61.1% of performance is jointly determined by these two variables, while the remaining percentage is influenced by other factors not examined in this study.